DigiMir Test: Establishing a Novel Pipeline for MiR-371a Quantification Using Droplet Digital PCR in Liquid Biopsies From Testicular Germ Cell Tumor Patients - Sequeira, José Pedro; Lobo, João; Constâncio, Vera; Brito-Rocha, Tiago; Carvalho-Maia, Carina; Braga, Isaac; Maurício, Joaquina; Henrique, Rui; Jerónimo, Carmen (Frontiers in Oncology, 2022)
Testicular germ cell tumors (TGCTs) are the most common cancers in young-adult males aged between 15-39 years. Hsa-miR-371a-3p is currently the most reliable biomarker for diagnosis and monitoring of these patients non-invasively in liquid biopsies, and it is destined to be introduced in the clinic due to improved performance compared to the classical serum tumor markers available. Current studies have focused on real-time quantitative PCR (RT-qPCR) protocols for its determination; still, some challenges remain, since these protocols often require preamplification steps (costly and time-consuming), and report relative levels normalized to a housekeeping microRNA, not always performed the same way. Droplet digital PCR (ddPCR) shows the promise to overcome these challenges, skipping normalization and preamplifications, but has hardly been explored in the field of TGCTs. In this work, we provide a report of a ddPCR-based pipeline for quantification of hsa-miR-371a-3p (the DigiMir pipeline) and compare it with two RT-qPCR protocols. A total of 107 plasma samples were investigated in the validation setting. The DigiMir pipeline detected TGCTs in a manner representative of tumor burden, with a sensitivity and specificity of 94% and 100%, respectively, outperforming the combined sensitivity of all three classical serum tumor markers (61.5%). Therefore, in this proof-of-concept investigation, we have showed that DigiMir pipeline constitutes a new promising methodology for accurately reporting hsa-miR-371a-3p in the clinical setting.